Exposure to sheep dip and the incidence of acute symptoms in a group of Welsh sheep farmers. Issue 4 (April 1996) - Rees, H
Abstract : OBJECTIVES: To measure the exposure of a group of farmers to organophosphate pesticide in sheep dip, and to record the incidence of symptoms after exposure. DESIGN: A prospective study of the autumn 1992 dipping period. Working methods were assessed by questionnaire. Absorption of organophosphate pesticide was estimated before, immediately after, and six weeks after dipping by measuring plasma cholinesterase, erythrocyte cholinesterase, and dialkylphosphate urinary metabolites of organophosphates. Symptoms were recorded by questionnaire at the same time as biological monitoring. Possible confounding factors were identified by medical examination of the subjects. SETTING: Three community council electoral wards in Powys, typical of hill sheep farming areas in Wales. SUBJECTS: All (38) men engaged in sheep dipping living in the three community council electoral wards. RESULTS: 23 sheep farmers and one dipping contractor completed the study–a response rate of 63%. A sample of seven men who refused to enter the full study had similar working practices to the 24 subjects. Subjects reported inadequate handling precautions, and significant skin contamination with dip. Two men reported under diluting dip concentrate for use. Both had significant depression of erythrocyte cholinesterase after dipping. This indicated some absorption of organophosphate pesticide–but this did not reach levels usually associated with toxicity. It was not clear whether the symptoms of these two mens were caused by organophosphate exposure. Measurement of dialkylphosphate urinary metabolites in a single specimen of urine voided shortly after the end of dipping could not be correlated with individual exposure. CONCLUSIONS: Sheep dipping is strenuous and dirty work and sheep farmers find it difficult to wear personal protective equipment and avoid skin contamination with dip. In this limited study, farmers did not seem to have significant organophosphate toxicity, despite using inadequate handling precautions.